2019
DOI: 10.9734/acri/2019/v16i230088
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microbial Contamination of Combs and Brushes in Beauty Salons within the University of Port Harcourt, Rivers State, Nigeria

Abstract: Beauty salons may provide a suitable medium for the growth and transfer of pathogenic microorganisms which may be of public health significance. This study was aimed at investigating the microbial contamination of beauty salon tools within the University of Port Harcourt, Rivers State, Nigeria. Nutrient agar was used for the determination of total culturable heterotrophic bacterial counts and Potato dextrose agar was used for the determination of total spore counts. Bacterial isolates were subjected to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 17 publications
5
15
3
Order By: Relevance
“…The results of this study agree with finding of a previous study which indicated the prevalence of bacterial colonies when hand air-dryers were used in washrooms ( Alharbi et al, 2016 ). Numerous previous studies have also confirmed the presence of bacterial contamination on tools used in barber shops ( Stanley et al, 2019 , Enemuor et al, 2013 , Janmohammadi et al, 2016 , Stanley et al, 2014 , Enemuor et al, 2012 , Naz et al, 2012 , Dadashi and Dehghanzadeh, 2016 ). Table 1 shows the prevalence of MRSA in barber shops where hair dryers were used.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The results of this study agree with finding of a previous study which indicated the prevalence of bacterial colonies when hand air-dryers were used in washrooms ( Alharbi et al, 2016 ). Numerous previous studies have also confirmed the presence of bacterial contamination on tools used in barber shops ( Stanley et al, 2019 , Enemuor et al, 2013 , Janmohammadi et al, 2016 , Stanley et al, 2014 , Enemuor et al, 2012 , Naz et al, 2012 , Dadashi and Dehghanzadeh, 2016 ). Table 1 shows the prevalence of MRSA in barber shops where hair dryers were used.…”
Section: Discussionmentioning
confidence: 60%
“…Daily interactions between people are the most obvious way in which pathogens are spread in communities ( Kramer et al, 2006 ). Fomites, such as hair dryers, scissors, combs and other tools used barber shops act as important pathogen-transmitters in barbers shops ( Kramer et al, 2006 , Stanley et al, 2019 , Adeleye and Osidip, 2004 , Barn and Chen, 2011 ), where every service can lead to the imposition of readily infectable skin-breaks ( Stout et al, 2011 ). Hairdressers, like barbers and their customers, are regularly exposed during their services to contamination by a wide range of both bacteria, some of which are potentially pathogenic ( Tharmila et al, 2012 , Enemuor et al, 2013 , Onajobi et al, 2015 , Janmohammadi et al, 2016 , Sekula et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial isolates were identified as Staphylococcus aureus , and species of Bacillus, Micrococcus, Serratia, Citrobacter, Proteus , and Shigella , and fungi such as Aspergillus flavus, Penicillium spp., Trichophyton spp., and Microsporum spp. 23 It can be concluded from this study that beauty salons can be considered a hazard when the hygiene standard is far from the expected, especially when it is combined with high moisture and dust content. Another study investigated the microbial content in a beauty blender when it was not cleaned at all or when it was dropped on the floor and reused without cleaning.…”
Section: Literature Reviewmentioning
confidence: 79%
“… 22 Fourth, the regular tools used in cosmetic salons such as razors, scissors, clippers, and nail care tools can accidentally penetrate the skin, which may lead to health problems ranging from inflamed skin to hepatitis. 23 Service providers themselves are susceptible to transferring infections among their customers if they suffer from serious medical problems. 4 , 10 , 24 Accordingly, several studies have been undertaken to determine if the transmission of viruses, bacteria, ring worm, or fungi is associated with cosmetic procedures in beauty salons.…”
Section: Literature Reviewmentioning
confidence: 99%